Talking About Life and Finding Solutions to Different Hardships: A Qualitative Study on the Impact of Narrative Enhancement and Cognitive Therapy on Persons With Serious Mental Illness - Roe, David (2010)
There is growing evidence that internalized stigma, or self-stigma, is a unique source of distress in the lives of people with severe mental illness. Narrative Enhancement and Cognitive Therapy is a structured group-based intervention aimed specifically at reducing internalized stigma and promoting recovery. The current study explores the therapeutic elements of the intervention and participants’ spontaneous reports of their experiences of the intervention, on the basis of a qualitative analysis of semi-structured interviews conducted with 18 people with severe mental illness who completed Narrative Enhancement and Cognitive Therapy. Qualitative analysis revealed 6 domains of improvement that participants attributed to their engagement in the intervention: Experiential learning, positive change in experience of self, acquiring cognitive skills, enhanced hope, coping, and emotional change. Processes identified as contributing to positive change included the therapeutic alliance and participants’ active role. The theoretical and practical implications of these findings are discussed.